2002
DOI: 10.1197/aemj.9.11.1156
|View full text |Cite
|
Sign up to set email alerts
|

Medical Errors—What and When: What Do Patients Want to Know?

Abstract: Regardless of health care utilization, a majority of respondents want full disclosure of medical error and wish to be informed of error immediately upon its detection. Respondents support reporting of errors to government agencies, the state medical board, and hospital committees focused on patient safety. Teaching physicians error disclosure techniques, honesty, and compassion were endorsed as a priority for educators who teach error management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…An important finding of our study is that 35.5% of respondents preferred to be informed of near miss ME. This is a much smaller percentage than the 88-92% reported in previous studies [15,27]. Interestingly, our study also showed that 30.4% of respondents perceived that the norm is to disclose near miss ME.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…An important finding of our study is that 35.5% of respondents preferred to be informed of near miss ME. This is a much smaller percentage than the 88-92% reported in previous studies [15,27]. Interestingly, our study also showed that 30.4% of respondents perceived that the norm is to disclose near miss ME.…”
Section: Discussioncontrasting
confidence: 77%
“…The American Society for Reproductive Medicine states that if there is clearly no adverse effect of a ME, disclosure may not be obligatory if it may unnecessarily increase patient's stress [26]. In the few empirical studies that have specifically addressed near miss ME, 88% to 92% of patients desired disclosure [15,27]. In contrast, most physicians opposed near miss ME disclosure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most medical professionals felt that DPSI is unnecessary in the case of near misses [17,22,28-32], but most of the general public believed the opposite [77]. Hearing about the occurrence of a near miss could upset patients, but it would alert patients to the type of medical errors that they should be cautious about and would reassure them that the medical systems designed to keep them safe were working [39].…”
Section: Discussionmentioning
confidence: 99%
“…Experts advocate that the initial disclosure discussion with the patient and their support person should occur as soon as possible after recognition of the adverse event ( 16 , 37 , 49 , 50 ). A delay in disclosure breeds uncertainty and evokes anxiety for the patient, support person(s), and their health care team.…”
Section: Acknowledging Complicationsmentioning
confidence: 99%